2017
DOI: 10.1089/thy.2016.0171
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Changes in Thyroid Hormones and Incident Type 2 Diabetes: A Seven-Year Longitudinal Study

Abstract: Individual changes in TSH and thyroid hormones, even within the normal reference range, were an additional risk factor of incident T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 41 publications
7
35
0
1
Order By: Relevance
“…The results of the present study are in line with the results of the cohort study from South Korea, where the baseline plasma TSH levels in the normal range were not associated with increased risk of incident T2DM [18]. Interestingly, the authors of that study found an association between an increase in plasma TSH levels over time and incident T2DM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the present study are in line with the results of the cohort study from South Korea, where the baseline plasma TSH levels in the normal range were not associated with increased risk of incident T2DM [18]. Interestingly, the authors of that study found an association between an increase in plasma TSH levels over time and incident T2DM.…”
Section: Discussionsupporting
confidence: 91%
“…of males (%)Reference range TSHAdjusted variablesChaker et al, 2016 [17]Netherlands, Rotterdam Study71886857.9 years12.1 per 1000 person-years64.6 years3553 (42%)0.4-4.0 mIU/LAge, sex, smoking, cohort, fasting serum glucose levels, fasting serum insulin, SBP, DBP, blood pressure lowering medication, HDL-C, BMIJun et al, 2017 [18]South Korea17,0619565.0 years11.2 per 1000 person-years50.5 years10,318 (60%)0.4–4.2 mIU/LAge, sex, smoking status, use of lipid drug, HbA1c, TG, HDL-C, LDL-C, hypertension, BMI, fasting glucose, family history of T2DMde Vries et al, 2017 (present study)Netherlands, SMART study55422895.6 years9.2 per 1000 person-years56.1 years3589 (65%)0.35-5.0 mIU/LAge, sex, current smoking, total and HDL-C, and TG, (fasting glucose, BMI, SBP, lipid lowering medication, blood pressure lowering medication) T2DM type 2 diabetes mellitus, TSH thyroid stimulating hormone, SBP systolic blood pressure, DBP diastolic blood pressure, HDL-C high-density lipoprotein cholesterol, LDL-C low-density lipoprotein cholesterol, BMI body mass index, HbA1c glycated hemoglobin A1c, TG triglycerides …”
Section: Resultsmentioning
confidence: 99%
“…In addition, our results revealed that no correlation and interaction exist between HbA1c and TSH. This finding is consistent with the previous report of a seven-year longitudinal study51, which suggests that the effects of high normal baseline HbA1c and TSH on the development of CHD may result from different pathological pathways, although the two parameters are related to glucose and lipid metabolisms. Hence, the combination of baseline HbA1c and TSH is valuable for identifying individuals who will later develop CHD.…”
Section: Discussionsupporting
confidence: 93%
“…Changes in serum TSH correlated with changes in glicaeted hemoglobin (HbA1c), which represents the main indicator of the average glycemic control over 2-3 months (117). The same group of authors reported that individual changes in TSH and thyroid hormones, even within the normal reference range, were an additional risk factor of incident T2DM during a seven-year longitudinal study on 6,235 euthyroid subjects without T2D (118). A progressive increase in TSH with a decrease in T3 and FT4, suggesting the development of a more severe form of hypothyroidism, was independently associated with the risk of developing T2D regardless of sex and thyroid autoimmunity.…”
Section: Changes In Tsh And/ or Th In Longitudinal Studies And Incidementioning
confidence: 98%